2017
DOI: 10.3390/app7060599
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Expansion Joint in Road Transition Curve: Effects Assessment on Heavy Vehicles

Abstract: Properly-designed road surfaces provide a durable surface on which traffic can pass smoothly and safely. In fact, the main causes that determine the structural decay of the pavement and its parts are the traffic loads. These repeated actions can create undesirable unevennesses on the road surface, which induce vertical accelerations on vehicles, up to hindering contact between pavement and tire, with dangerous consequences on traffic safety. The dynamic actions transmitted by the vehicles depend on these irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Data analysis research, based on displacement gauges from structural health monitoring (SHM) systems, has been conducted. A variety of methods, including correlation ftting [3,[7][8][9][10][11], mechanical performance analysis of bridge structures [12][13][14][15], Bayesian approaches [16,17], statistical machine learning [18], and data reconstruction [19,20], have been utilized to examine the displacement patterns of BEJs for damage evaluation. Te fndings indicate that the wear damage of BEJs is primarily due to large cumulative displacements, which are signifcantly infuenced by temperature and trafc loading.…”
Section: Introductionmentioning
confidence: 99%
“…Data analysis research, based on displacement gauges from structural health monitoring (SHM) systems, has been conducted. A variety of methods, including correlation ftting [3,[7][8][9][10][11], mechanical performance analysis of bridge structures [12][13][14][15], Bayesian approaches [16,17], statistical machine learning [18], and data reconstruction [19,20], have been utilized to examine the displacement patterns of BEJs for damage evaluation. Te fndings indicate that the wear damage of BEJs is primarily due to large cumulative displacements, which are signifcantly infuenced by temperature and trafc loading.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [9,10] investigated the effects of EJ damage (simplified as road roughness) on the vehicle-induced dynamic response of the deck slabs of a prestressed concrete box girder bridge by using a proposed multi-degree-of-freedom vehicle model, and indicated that the EJ damage can increase the vehicle-induced impact on the deck slabs and EJ. Di et al [11] constructed a three-dimensional numerical analysis model of an EJ system and then investigated the dynamic response and damage state of an EJ under heavy vehicle loads. Li et al [12] carried out the field testing of 150 EJs and pointed out the diseases of EJs commonly experience, which would aggravate the vehicle-induced impact response of the EJs and the side bridge.…”
Section: Introductionmentioning
confidence: 99%
“…In past studies, many scholars have studied bridge expansion joints [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Winkler et al [ 16 ] proposed a method to collect bridge expansion joint data.…”
Section: Introductionmentioning
confidence: 99%